MENTAL FEATURES OF THE FORMATION OF THE LEGAL CULTURE OF MODERN YOUTH (Journal of actual problems of jurisprudence, 2025)
The article is devoted to the study of the issues of legal culture of youth in modern Kazakhstani society. The purpose of the article is to study the level of legal culture of young people, their knowledge and ability to apply their rights in practice, as well as legal nihilism in the minds of young people. At the same time, the article considers the meaning and concept of legal culture, its various definitions, as well as its importance in the creation of a legal state and civil society. This scientific work is developed on the basis of the analysis of scientific research of domestic and foreign scientists on the issue under consideration and the results of empirical research of the authors. The purpose of the article is to identify patterns and reasons for the formation of the legal culture of Kazakhstani youth. For this purpose, a sociological survey was conducted among students of the Kazakh National University named after al-Farabi in order to identify their perception of legal culture and its level. In total, more than 300 students of 1-4 courses of legal and economic specialties took part in the survey. The conducted research is distinguished by the following main factors: the interest of young people in legal issues, the situation in society with human rights and freedoms, mistrust of law enforcement agencies, a low level of civic activity, legal nihilism and many others. These features indicate a low level of youth involvement in the human rights protection system in the country, the incompleteness of the formation of civil society, the absence of an effective system for raising the level of legal culture, the absence of a system for disseminating legal information and using legal knowledge. All this complicates the process of legal development of young people and the formation of a state based on the rule of law, and as a result, the development of civil society slows down. In conclusion, the article proposes legislative changes to form a legal culture among young people in society.      Keywords: legal culture, rule of law, legal nihilism, mental uniqueness, values, youth, generation Z